Analysis of how a teacher-centered class hinders Interactive communication of second grade students of Colegio Americano de Guayaquil. - Mejía Ortega, María Gabriela (2017)
The main goal of this research project is to analyze how a teacher-centered class hinders interactive communication of second grade students of Colegio Americano de Guayaquil. The specific objectives are to explain the effects teacher-centered education has on students’ learning process, to determine what kind of instruction boots interactive communication in the classroom, and to decide which methods and techniques enhance interaction among students. The research methods used in this case study were a mix of qualitative and quantitative approaches. The data collection was made with a survey to know about students’ learning experiences, and through observation of their communicative abilities recorded in a rubric. Thanks to the information gathered, it can be concluded that a teac her-centered class negatively affects interactive communication of students since such approach does not utilize practices and procedures that promote real interaction among students.